1996
DOI: 10.1007/bf02507108
|View full text |Cite
|
Sign up to set email alerts
|

Role of fibroblasts in the regulation of proinflammatory interleukin IL-1, IL-6 and IL-8 levels induced by keratinocyte-derived IL-1

Abstract: In the epidermis, the keratinocytes are the first cells to be encountered by external stimuli and they are able to promote the inflammatory response by increased production and release of various cytokines. In their turn, these cytokines may directly affect the production of proinflammatory cytokines in human dermal fibroblasts. In addition, in both epithelial and mesenchymal cells cytokine production may be modu lated by their mutual interaction, and thereby regulate the inflammatory response. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 32 publications
3
64
0
1
Order By: Relevance
“…This interaction can be based upon 1) production of soluble factors by either epithelial (after being activated by, for example, growth factors) or mesenchymal cells that exhibit autocrine and/or paracrine activities, 2) cell-matrix interactions, or 3) signaling by direct cell-cell contact. Through the release of interleukin-1, keratinocytes can enhance the release of growth factors such as granulocyte-macrophage colony-stimulating factor, IL-6, or IL-8 in dermal cells, which in turn stimulate basement membrane formation (42)(43)(44)(45). Thus, we have demonstrated that, in the absence of fibroblasts, EGF can be used as a substitute to provide keratinocyte growth and differentiation and can also stimulate ECM1 as well as PLSCR1 expression.…”
Section: Discussionmentioning
confidence: 78%
“…This interaction can be based upon 1) production of soluble factors by either epithelial (after being activated by, for example, growth factors) or mesenchymal cells that exhibit autocrine and/or paracrine activities, 2) cell-matrix interactions, or 3) signaling by direct cell-cell contact. Through the release of interleukin-1, keratinocytes can enhance the release of growth factors such as granulocyte-macrophage colony-stimulating factor, IL-6, or IL-8 in dermal cells, which in turn stimulate basement membrane formation (42)(43)(44)(45). Thus, we have demonstrated that, in the absence of fibroblasts, EGF can be used as a substitute to provide keratinocyte growth and differentiation and can also stimulate ECM1 as well as PLSCR1 expression.…”
Section: Discussionmentioning
confidence: 78%
“…(17) Moreover, many studies have confirmed the production of cytokines like IL-8 by cancer cells and the increase of their receptors in premalignant lesions such as Lichen planus (18) and SCC. (19,20) IL-8 and VEGF which are expressed simultaneously in head and neck carcinoma cells (HNSCCs) and a number of other cells, induce tumoral growth, angiogenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the epithelial-mesenchymal interaction plays an important role in establishing the profile of released factors regulating proliferation and differentiation of keratinocytes. This interaction can be based on (i) production of soluble factors by either epithelial or mesenchymal cells that exhibit autocrine and/or paracrine activities, 24,27,[36][37][38][39][40] (ii) cell-matrix interactions 41 (iii) signaling by direct cell-cell contact. 42 The lower re-epithelialization rate in full-thickness wounds is indicative that in addition to paracrine cytokine and growth factor action, the crosstalk between keratinocytes and fibroblasts are important regulators of keratinocyte proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%